2007
DOI: 10.1002/uog.3923
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum evaluation of the anal sphincter by transperineal three‐dimensional ultrasound in primiparous women after vaginal delivery and following surgical repair of third‐degree tears by the overlapping technique

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…However, one should be aware that when using these methods not all anal sphincter defects will be identified. The recent use of 3D TPU in post-partum women is promising, 31 but needs to be compared to EAU.…”
Section: Discussionmentioning
confidence: 99%
“…However, one should be aware that when using these methods not all anal sphincter defects will be identified. The recent use of 3D TPU in post-partum women is promising, 31 but needs to be compared to EAU.…”
Section: Discussionmentioning
confidence: 99%
“…The images obtained included both longitudinal and transverse views. Each internal and external anal sphincter were carefully examined in the axial plane to assess continuity, and the presence or absence of a defect was recorded, as previously reported [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…Early recog nition, particularly during the immediate postpartum period, and surgical repair are fundamental to reduce later anal incontinence [46] . Four ultrasonographic signs indicative of damage after repair were defined as EAS or IAS sphincter discontinuity, thickening of the EAS at the 12o'clock position, thinning of the IAS in the area of rupture in conjunction with thickening opposite the rupture site (the "halfmoon" sign), and abnormality of the mucous folds [47,48] . The PREDICT [49] study revealed that 2D TPUS had a sensitivity and specificity of 64% and 85%, respectively, for detecting sphincter defect when compared with EAUS.…”
Section: Fecal Incontinencementioning
confidence: 99%
“…There are several studies showing that 3D TPUS is an accessible, inexpensive and confortable method, allowing good sphincter evaluation in the postpartum period and also following surgical repair [47,48,53] . This technique has a multiplanar image, more precise volume calculation, and shorter examination period, with a possibility for a second opinion consultation, without the presence of the patient [47] .…”
Section: Fecal Incontinencementioning
confidence: 99%
See 1 more Smart Citation